PENGARUH DISIPLIN KERJA DAN PENGAWASAN MELEKAT TERHADAP EFEKTIVITAS KERJA PEGAWAI SEKRETARIAT DAERAH KABUPATEN BOGOR - Yasnimar Ilyas; Trio Nugroho Saputro (Economicus : Jurnal Ekonomi dan Manajemen, 2020)
The purpose of this study was to determine the effect of inherent work discipline and supervision on the work effectiveness of employees at the Bogor District Secretariat Office. In this studyhe sampling was done by the saturation sampling method that is the number of samples equal to the total population of 95 employees. The results showed that the results of the partial hypothesis test showed that the work discipline and inherent supervision variables had a positive and significant effect on the work effectiveness of the Bogor Regency Secretariat staff where the t value of each variable was greater than the t table value. Simultaneous hypothesis test results obtained P value of 10,793 with a value of Siq.0,000 <0.05. This proves that simultaneous work discipline and inherent supervision have a positive and significant influence on the work effectiveness of Bogor Regency Regional Secretariat staff. The coefficient of determination test results obtained Adjusted R square value of 0.372 or 37.2%. This shows that work discipline and inherent supervision contribute to the work effectiveness of Bogor Regency Regional Secretariat employees by 37.2% while the remaining 62.8%, employee work effectiveness is influenced by other factors in the study.